Variation in virulence of Septoria tritici Rob ex Desm isolates on wheat - Perelló, Analía Edith (1991)
To identify physiologic races, the variation in virulence of 10 local Septoria tritici Rob ex Desm isolates was evaluated on 10 wheat differentials selected in Israel and 7 previously tested Argentine cultivars (cvs). Pycnidial leaf coverage percentage (PC) and necrotic lesion percentage (NL) were used to determine cvs reaction in order to compare their efficiency in isolate differentiation. Isolates behaved differently on the different wheat cvs. The 2 variables showed which isolates behaved similarly, and which behaved differently; PC was more sensitive in detecting these differences. The ranking of varieties for PC and NL was different for every isolate x cv combination, and few ordering patterns coincided (Bobwhite "S", lassul 20 and Bordenave Puan). In general, local isolates induced more PC than NL on national cvs. Two isolates (IIbehaved in the most virulent manner; 2 others (IIprovoked the highest resistant reaction percentage on the cvs tested. Isolate x cv interaction varied according to the parameter evaluated. The analysis of variance for PC indicated significant interaction between the 2 main factors (P = 0.01) which may be considered as an index of pathogen physiologic specialization. However, a non-significant interaction (P = 0.01) for NL indicated only differences between isolates degree of aggressiveness. Low degree of specificity of the interactions and similar order in the ranking of disease severity on some cvs showed no "true physiologic races". The international set did not supply any major variation range in lesion type and percentage or more consistent cv reactions in differentiating biotypes. Thus, the standardization of research methodologies is necessary to study S tritici-Triticum sp interactions. This would contribute to the reproducibility of results obtained by different authors throughout the world and thus avoid different interpretations of varietal reaction.